2020
DOI: 10.1002/jocb.472
|View full text |Cite
|
Sign up to set email alerts
|

The Process of Art‐making and Creative Expertise: An Analysis of Artists' Process Modification

Abstract: The present study investigates how emerging/young and established/expert artists create artwork, paying special attention to modifications in the art‐making process. Here, “process modification” is the means by which artists generate new artistic concepts by modifying elements of their previous artwork. To examine whether emerging artists use such modifications in the same manner as experts, we interviewed 28 contemporary artists (including 14 experts). The results reveal that most of the emerging artists modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
(66 reference statements)
1
8
0
Order By: Relevance
“…Most programs and studies have not paid sufficient attention to broad and comprehensive ways to facilitate creativity and support the concept and vision generation. This study proposed the importance of the creativity dynamics approach with the ultimate goal of generating concepts and visions from a long-term perspective based on the theory of creative expertise (e.g., Okada et al, 2009;Shimizu & Okada, 2018;Yokochi & Okada, 2020). This approach also referred to the systems model (Csikszentmihayli, 1988(Csikszentmihayli, , 2014 and the 5A approach (Glaveanu, 2013) that strongly proposed the importance of interaction among people and the environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most programs and studies have not paid sufficient attention to broad and comprehensive ways to facilitate creativity and support the concept and vision generation. This study proposed the importance of the creativity dynamics approach with the ultimate goal of generating concepts and visions from a long-term perspective based on the theory of creative expertise (e.g., Okada et al, 2009;Shimizu & Okada, 2018;Yokochi & Okada, 2020). This approach also referred to the systems model (Csikszentmihayli, 1988(Csikszentmihayli, , 2014 and the 5A approach (Glaveanu, 2013) that strongly proposed the importance of interaction among people and the environment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study of novices' art creation showed that by incorporating others' perspectives by copying others' artwork, people can change their own perspective of creation and generate novel works (Okada & Ishibashi, 2017). As for the third component, studies on the development of creative expertise suggest that the long-term exploratory process plays a critical role in the creative expertise development (Okada, Yokochi, Ishibashi, & Ueda, 2009;Shimizu & Okada, 2018;Yokochi & Okada, 2020). We have previously mentioned the details of this component.…”
Section: Figure 1 Outline Of the Creativity Dynamics Approach Framework By Repeating This Dynamical Developmental Process People Graduallmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, science communicators may use an internal goal or motivation [Moravcsik, 1974], such as personal enjoyment, creative self-expression, or finding beauty, to help them create work that others will enjoy [Brown Jarreau, 2015a]. Internal goals as well as personal interests, experiences, and intentions may be particularly important to the artist's creation process [Yokochi & Okada, 2021].…”
Section: Internal Goals In Sciartmentioning
confidence: 99%
“…By studying the cognitive performance or processes of experts, psychologists have been able to ascertain basic inferences about the mind and brain (e.g., Dottori et al, 2020; Sella & Kadosh, 2018), as well as more applied findings that center around developmental, educational, or organizational phenomena (Alexander, 2003; Gobet, 2005). As part of this line of inquiry, psychologists have recruited a wide variety of experts in their research including chess masters (Bilalić et al, 2010), fighter pilots (Boyd et al, 2005), emergency room physicians (Redelmeier, 2005), and, increasingly in recent years, highly regarded professional creative artists (Yokochi & Okada, 2021).…”
Section: Why Study Professional Actors?mentioning
confidence: 99%